DETERMINATION OF RATIONAL COMPOSITION AND CONCENTRATION OF SUPERFINE ALUMINIUM MODIFIER FOR MODIFYING OF THE ALLOY AK18 STRUCTURE - V. Ju. Stetsenko; A. P Gutev (Литьë и металлургия)
It is shown that for reaching of maximal effect of mo difying of alloy AK18 structure it is necessary to use super fine aluminium modifier AlSi12Sb15Ti5 in the quantity of 0,1% of melt mass or AlSb5Ti3 at the quantity of 0,5%.